Preparation of triangular silver nanoparticles and their biological effects in the treatment of ovarian cancer - Man Yin; Xiangyu Xu; Hui Han; Jiahui Dai; Ronghe Sun; Linqing Yang; Junyu Xie; Yunfei Wang (BMC, 2022)
Abstract Background In recent years, silver nanoparticles (AgNPs) have gradually been widely used, especially in the field of anticancer medicine. Ovarian cancer (OC) is the gynaecological malignancy with the highest mortality rate, and the current treatment is still based on surgery, chemotherapy and postoperative targeted therapy. Therefore, the development of safe and effective nanoparticles for targeted therapy of OC is very important. This study aimed to prepare a new type of triangular silver nanoparticles (tAgNPs) and evaluate the anticancer properties for OC in vitro and in vivo. Methods The tAgNPs were chemically synthesized and characterized using scanning electron microscopy (SEM), ultraviolet (UV) spectrophotometry and other techniques. By performing cell-based tests, such as cell counting kit-8 (CCK-8), plate colony formation, cell apoptosis, reactive oxygen species (ROS), and western blot (WB) assays, the inhibitory effects and related mechanisms of tAgNPs on OC cells were analysed.The anticancer effect of tAgNPs in vivo was verified by a SKOV3 tumor-bearing mouse model. Results Five types of tAgNPs with different colours were successfully synthesized, with a particle size of 25-50 nm and a good dispersion. The results of in vitro experiments showed that tAgNPs treatment reduced the viability and proliferation of SKOV3 cells, arrested the cell cycle in G0/G1 phase, inhibited the expression levels of proliferation-related factors and cyclins, and promoted cell apoptosis by producing ROS and increasing caspase-3 activity. Consistent with the results of in vitro experiments, in vivo animal experiments also showed that tAgNPs significantly inhibited the proliferation of ovarian cancer. More importantly, no obvious toxic and side effects were observed. Conclusions In this study, a novel triangular AgNPs was successfully prepared. tAgNPs are very stable, significantly inhibit the proliferation of OC cells and tumour growth in tumour-bearing mice, providing a promising nanotargeted therapy for OC.